PATTERN AND PROGRESSION OF CHRONIC KIDNEY DISEASE IN A GROUP OF PATIENTS IN SULAIMANI CITY - Munthir, Neiran; Sharif, Dana A; Ismail, Serwan M; Abdul, Rbaz Jamal (Journal of Sulaimani Medical College, 2025)
Background Chronic kidney disease (often underdiagnosed, and its complications often undertreated) is a worldwide public health problem associated with a signifi cant increase in mortality. Objective To fi nd out the common causes of chronic kidney disease in Sulaimani to prevent and accurately assess risk factors for target intervention to prevent or slow down the progression. Patients and Methods An observational case series study was accomplished on 192 patients with chronic kidney disease in Sulaimani City from September 2018 to March 2019. Following informed consent, a questionnaire collected demographic and clinical details. Laboratory data of the patients were also collected and statistically analyzed. Results The majority (58.9%) of the participants were 18-64 years old, 66.7% lived in urban areas, and 66.1% had a low socioeconomic status. The leading causes of chronic kidney disease in children were glomerular diseases (45.4%) and congenital urological malformations (31.8%), while in adults and elderly group, diabetic nephropathy (25.9%), glomerular diseases (19.4%), and hypertension (16.5%) were the most common causes. About 50% of all patients were diagnosed when they reached advanced stages (stage IV, V), and about 90% of patients diagnosed at early stages progressed to advanced stages. Uncontrolled diabetes, proteinuria (≥ 1gm), and uncontrolled blood pressure were signifi cant risk factors for progression. Conclusion Chronic kidney disease is underdiagnosed and undertreated in our region. Early detection and measures to slow disease progression should be encouraged.
Keywords: chronic kidney disease; predictors; progression; risk factors for progression